SOCIAL MEDIA MARKETING AND CELEBRITY ENDORSEMENT IMPACT ON PURCHASE INTENTION MEDIATED BY BRAND AWARENESS - Laurence, Angelica; Ekawati , Sanny (International Journal of Application on Economics and Business, 2025)
The significant expansion of the cosmetics industry has led to heightened competition, compelling businesses to identify key factors that drive consumers' purchase intentions. This study concentrates on examining the elements influencing the purchase intention for Implora cosmetics. A descriptive research approach was applied, using purposive sampling to obtain responses from 275 participants through questionnaires. The data were examined using PLS-SEM to investigate the connections between these four variables. The results indicated that social media marketing, celebrity endorsements, and brand awareness are able to affect consumers' intention to buy Implora products. Additionally, it was found that brand awareness can acts as a mediator between social media marketing and the intention to purchase, as well as between celebrity endorsement and the intention to purchase Implora products. the influence of social media marketing and celebrity endorsements on the intention to purchase. These results underscore the crucial function of these three factors in improving purchase intentions, suggesting that focusing on social media marketing, celebrity endorsements, and brand awareness can help strengthen competitiveness in the market.